(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1862)
A description of the design and dimensions of the tower at Brechin. The author argues that the decoration on the tower’s doorway was a later addition to the structure, and goes on to suggest that the roof may also have been a later addition. He discuss several other examples of towers in Ireland where he believed Christian symbols were added to already existing pre-Christian structures and concludes his paper by arguing that since human remains were unearthed from beneath many of these towers, they were likely memorial monuments. In a note after the article, several Fellows including the Secretary, John Stuart, disagreed with the author’s conclusions about the later additions to the tower.